Battery Energy Storage System for PV Output Power Leveling. (16th December 2014) - Singh, Rajkiran; Taghizadeh, Seyedfoad; Tan, Nadia Mei Lin; Pasupuleti, Jagadeesh
Abstract : Fluctuating photovoltaic (PV) output power reduces the reliability in power system when there is a massive penetration of PV generators. Energy storage systems that are connected to the PV generators using bidirectional isolated dc-dc converter can be utilized for compensating the fluctuating PV power. This paper presents a grid connected energy storage system based on a 2 kW full-bridge bidirectional isolated dc-dc converter and a PWM converter for PV output power leveling. This paper proposes two controllers: a current controller using the d-q synchronous reference and a phase-shift controller. The main function of the current controller is to regulate the voltage at the high-side dc, so that the voltage ratio of the high-voltage side (HVS) with low-voltage side (LVS) is equal to the transformer turns ratio. The phase-shift controller is employed to manage the charging and discharging modes of the battery based on PV output power and battery voltage. With the proposed system, unity power factor and efficient active power injection are achieved. The feasibility of the proposed control system is investigated using PSCAD simulation.